DOES FISHER EFFECT HOLD IN SRI LANKA? AN ANALYSIS WITH BOUNDS TESTING APPROACH TO COINTEGRATION - Jayasinghe, Prabath (My University, 2012)
Fisher Hypothesis implies a one-to-one long-term relationship between nominal interest rate and inflation. Though this one-to-one relationship does not hold in most of the financial markets, there exists strong evidence for a partial relationship between the two variables. This study inquires into the longterm relationship between nominal interest rate and inflation in the context of Sri Lankan financial markets. The study has two prime objectives. First, it examines the nature of the relationship between nominal interest rate and inflation in Sri Lanka. Second, it investigates whether there exists differences in this relationship across different frequencies of data such as monthly, quarterly and annual. As an alternative to the various methodologies used to test for Fisher Hypothesis with data for Sri Lanka, this study employs Autoregressive Distributed Lag bounds testing approach developed in Pesaran, Shin and Smith (2001). The main finding of the study is the evidence for the absence of a long-term relationship between nominal interest rate and inflation in Sri Lankan financial markets.